2016
DOI: 10.1136/heartjnl-2016-309735
|View full text |Cite
|
Sign up to set email alerts
|

Pre-procedural dual antiplatelet therapy in patients undergoing transcatheter aortic valve implantation increases risk of bleeding

Abstract: UMIN-ID; 000020423; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 29 publications
2
31
2
Order By: Relevance
“…Patients' characteristics and the outcomes in the present study are comparable to those reported in other Japanese studies. 7,11,24, 25 On the other hand, despite similar mean STS scores, the mortality and readmission rates in the present study were lower than those of a US registry, probably because of our learning curve. 26 This present data did not include our initial experience with patients who were in the Japanese trial that began in 2010.…”
Section: Impact Of Frailty Markers In Tavicontrasting
confidence: 51%
“…Patients' characteristics and the outcomes in the present study are comparable to those reported in other Japanese studies. 7,11,24, 25 On the other hand, despite similar mean STS scores, the mortality and readmission rates in the present study were lower than those of a US registry, probably because of our learning curve. 26 This present data did not include our initial experience with patients who were in the Japanese trial that began in 2010.…”
Section: Impact Of Frailty Markers In Tavicontrasting
confidence: 51%
“…Staged PCI before TAVR may limit TAVR duration and contrast media volume compared with concomitant PCI. However, it imposes a pre‐procedural use of dual antiplatelet therapy, which may be associated with an increased risk of hemorrhagic complications . Further studies, such as the ACTIVATION trial are warranted to better define the optimal management of this high‐risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with no pre-procedure antiplatelet did not have an increase in thromboembolic risk. 20 Compared to DAPT, aspirin alone was associated with lower composite outcomes and bleeding in these small studies. Larger clinical trials are necessary to assess the comparative efficacy of aspirin alone versus DAPT versus oral anticoagulation based strategies to achieve optimal outcomes after TAVR .…”
Section: Subclinical and Clinical Leaflet Thrombosismentioning
confidence: 71%
“…In multivariate analysis, DAPT before TF‐TAVR significantly increased bleeding compared with SAPT (adjusted OR 2.05, P = 0.014) and no antiplatelet therapy (adjusted OR 2.30, P = 0.031). Patients with no pre‐procedure antiplatelet did not have an increase in thromboembolic risk Compared to DAPT, aspirin alone was associated with lower composite outcomes and bleeding in these small studies.…”
Section: Adjunctive Therapies and Imaging In Tavrmentioning
confidence: 99%